DLX3 interacts with GCM1 and inhibits its transactivation-stimulating activity in a homeodomain-dependent manner in human trophoblast-derived cells - Sha Li (Nature Portfolio, 2017)
Abstract The placental transcription factors Distal-less 3 (DLX3) and Glial cell missing-1 (GCM1) have been shown to coordinate the specific regulation of PGF in human trophoblast cell lines. While both factors independently have a positive effect on PGF gene expression, when combined, DLX3 acts as an antagonist to GCM. Despite this understanding, potential mechanisms accounting for this regulatory interaction remain unexplored. We identify physical and functional interactions between specific domains of DLX3 and GCM1 in human trophoblast-derived cells by performing immunoprecipitation and mammalian one hybrid assays. Studies revealed that DLX3 binding reduced the transcriptional activity of GCM1, providing a mechanistic explanation of their functional antagonism in regulating PGF promoter activity. The DLX3 homeodomain (HD) was essential for DLX3-GCM1 interaction, and that the HD together with the DLX3 amino- or carboxyl-terminal domains was required for maximal inhibition of GCM1. Interestingly, a naturally occurring DLX3 mutant that disrupts the carboxyl-terminal domain leading to tricho-dento-osseous syndrome in humans displayed activities indistinguishable from wild type DLX3 in this system. Collectively, our studies demonstrate that DLX3 physically interacts with GCM1 and inhibits its transactivation activity, suggesting that DLX3 and GCM1 may form a complex to functionally regulate placental cell function through modulation of target gene expression.